2009
DOI: 10.1364/oe.17.015534
|View full text |Cite
|
Sign up to set email alerts
|

Who needs a cathode?
Creating a second-order nonlinearity by charging glass fiber with two anodes

Abstract: We report that it is possible to create a fiber electret by having both internal electrodes of a twin-hole fiber at the same anodic potential, i.e., without the use of a contacted cathode electrode. We find that a stronger and more temperature-stable charge distribution results when the fiber core is subjected to an external field near zero. Negative charges from the air surrounding the fiber are sufficient for the recording of an electric field across the core of the fiber that is twice stronger than when one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
37
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 18 publications
2
37
0
Order By: Relevance
“…Since the first reports of the thermal poling of silica fibers almost 25 years ago now, a number of more recent efforts have focused on exploring alternative electrode configurations [1,2] in order to gain both a deeper understanding and to develop more robust methods of device fabrication. In particular, the observation [1] that two internal fiber electrodes at the same positive potential generate a more efficient and stable second order nonlinearity than the conventional positive-negative configuration is at first glance highly counter-intuitive, as the electric field gradient at the midpoint between the two anodes (close to where the poled light guiding core is located) is very small.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the first reports of the thermal poling of silica fibers almost 25 years ago now, a number of more recent efforts have focused on exploring alternative electrode configurations [1,2] in order to gain both a deeper understanding and to develop more robust methods of device fabrication. In particular, the observation [1] that two internal fiber electrodes at the same positive potential generate a more efficient and stable second order nonlinearity than the conventional positive-negative configuration is at first glance highly counter-intuitive, as the electric field gradient at the midpoint between the two anodes (close to where the poled light guiding core is located) is very small.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the observation [1] that two internal fiber electrodes at the same positive potential generate a more efficient and stable second order nonlinearity than the conventional positive-negative configuration is at first glance highly counter-intuitive, as the electric field gradient at the midpoint between the two anodes (close to where the poled light guiding core is located) is very small. However, Margulis et al [1] proposed an "avalanche-like" positive feedback mechanism to explain this poling behaviour, as positive ions migrating away from the anodes immediately lead to a rapid increase in glass resistivity, thus leading to an increase in potential difference at the midpoint. Even more charge movement and larger potential difference between the anodes and fiber midpoint then begins to accumulate until the poling process is completed.…”
Section: Introductionmentioning
confidence: 99%
“…When the sample is cooled down whilst the voltage is still applied, an electric field is frozen into the depleted region and an effective nonlinear susceptibility ( ) is induced into the sample due to a process of third order nonlinear optical rectification. The early issues mainly related to the high risk of breakdown between the two electrodes (typically separated by a few tens of microns) were addressed by Margulis et al [6], who demonstrated that it is possible to induce a value of ( ) higher than the one obtained in the conventional case[5] by means of a poling configuration in which the two embedded electrodes are both connected to the same positive potential of the anode. The method for "charging" optical fibers has been recently further developed by De Lucia et al [7], who discovered that it is possible to create a space charge region using electrostatic induction between an external inductor and the floating electrodes embedded inside a fused silica twin-hole fiber.…”
mentioning
confidence: 99%
“…When the sample is cooled down whilst the voltage is still applied, an electric field is frozen into the depleted region and an effective nonlinear susceptibility ( ) is induced into the sample due to a process of third order nonlinear optical rectification. The early issues mainly related to the high risk of breakdown between the two electrodes (typically separated by a few tens of microns) were addressed by Margulis et al [6], who demonstrated that it is possible to induce a value of ( ) higher than the one obtained in the conventional case…”
mentioning
confidence: 99%
See 1 more Smart Citation